PENGEMBANGAN E-JOBSHEET DENGAN LIVEWORKSHEET UNTUK MENINGKATKAN EFEKTIVITAS PRAKTIK SISWA SMK - Amriansyah Alfia; Sardianto Markos Siahaan; Ketang Wiyono; Makmum Raharjo; Erna Retna Safitri (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This study uses the Research and Development method which is applied to product assembly skills. This research targets the students of class XII TKR SMKN 1 Sungai Lilin. The research model used was Alessi & Trollip, while the validators came from experts in their respective fields related to this research: material, media, and language experts. This research has produced a valid, practical, and effective product on the product assembly skills e-job sheet to increase the effectiveness of Vocational High School students practice. Material professional validation acquired a rating of 87.2, media professional 87.1, and linguist 88.3 in order that the product evolved became a totally valid category, with a practicality degree of 83.4 labeled as very practical, and an e-job sheet with a powerful live worksheet for growing the meeting of items merchandise with a cost of tcount > ttabel, specifically 16.491 > 2.015 or sig. (2-tailed) < 0.05.